Experiment and analysis on the heterogeneity of CO2 adsorption-transport by microrocks in coal matrix - Guosong Jing; Qian Zhao; Ziqiang Jin (PLoS ONE, 2025)
In order to study gas adsorption performance effected by micro-rock in coal matrix, dual energy X-ray CT was used to calculate the density change of coal core before and after gas injection, which can obtain the CO2 concentration (adsorption amount) in coal core, and reveal the uneven characteristics of CO2 adsorption by minerals. The research results show that coal core in the region where minerals exist has a higher density, while the density of the coal matrix is smaller. Regions with higher coal density (more minerals) have weaker adsorption capacity for CO2. The CO2 concentration in coal core decreases approximately linearly along the axial direction of coal core from the gas injection end to the outlet section. The average voxel density is basically the same at the same coal core section before and after gas injection, which indicates that the coal matrix recovers and approaches the original state after desorption. However, before and after gas injection, the average voxel density of coal core varies greatly, and the frequency variation and average deviation factor of different voxel densities vary greatly, which indicates that the adsorption of CO2 by coal core is extremely uneven.